Harmonizing conjugated and non-conjugated emission for amorphous blue organic afterglow through copolymerization and aggregation engineering. Issue 44 (7th November 2022) - Zhang, Longyan; Peng, Hao; Zhang, Jingyu; Guo, Zhenli; Jin, Yishan; Zhang, Shuwei; Tao, Ye; Zheng, Chao; Chen, Runfeng
Abstract : High-performance water-responsive OURTP polymers with simultaneously elongated lifetimes and improved efficiency were achieved by harmonizing cluster-triggered emission and conjugated luminance. Abstract : Organic afterglow with ultralong room-temperature phosphorescence (OURTP) has attracted extensive attention recently, but remains an intrinsic challenge in boosting the OURTP performance with simultaneously elongated lifetimes ( τ p ) and improved quantum yields ( Φ p ), especially for amorphous OURTP. Here, a synergistic strategy is proposed to modulate both Φ p and τ p by harmonizing the non-conjugated cluster-triggered emission with conjugated aromatic luminance in flake form through copolymerization and aggregation engineering. High-performance amorphous blue (442 nm) OURTP with simultaneously elongated τ p and improved Φ p over 108- and 9-fold has been achieved, reaching 4.2 s and 15.5% respectively. More impressively, this strategy is extendable to other conjugated/non-conjugated copolymers; OURTP intensity and lifetime can also be simultaneously boosted with significant water responsibility. With these extraordinary stimuli-responsible OURTP polymers, rewritable encryption papers are constructed, on which high-resolution anti-counterfeiting patterns can be water-jet printed and multi-color and multi-level encryption is realized by energy transfer from the blue OURTP polymer to commercial dyes. This work not only demonstrates an efficient strategy for designing efficient OURTP polymers with a high afterglow performance but also offers a new avenue to modulate amorphous OURTP for multi-color and stimuli-responsive afterglow and advanced encryption applications.